National Ambulatory Medical Care Survey, 1981: Drug Mentions ([Verlag nicht ermittelbar], 1989)
This data collection is the latest in a series of surveys that offer information on patients' visits to a national sample of office-based physicians. The National Ambulatory Medical Care Surveys (NAMCS) collect information on all drugs/medications ordered, administered, or provided during the visits. In 1981 45,610 drugs were mentioned in the national sample of 43,366 patient visits. The data items include the medication code, generic name and code, brand name, entry status, prescription status, federal controlled substance status, composition status, and related ingredient codes.